Effectiveness of Mulu Bebe Banana Peel (Musa acuminata) as an Edible Coating Alternative to Increase the Shelf Life of Tomatoes - Runaweri, Christian; Manikome, Nonice (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Researchers conducted research on the effectiveness of mulu bebe banana peel as an alternative edible coating to increase the shelf life of tomatoes. This research aims to find a method for making edible coating from Mulu Bebe banana peel with several concentrations so that it can extend the shelf life of tomatoes. The benefit of this research is to extend the shelf life of tomatoes. The research was carried out from June to September 2023, carried out at the BASIC SCIENCE Laboratory at Hein Namotemo University. Things that were observed were changes in the texture, color and weight of the tomatoes during the day of observation. The results of the research on changes in the texture of tomatoes, tomatoes without treatment (concentration 0%) until the twelfth day of observation, the surface of the fruit skin began to wrinkle and when held the tomatoes were no longer hard (soft and rotting), in contrast to tomatoes with treatment, edible concentration coating 20% and 25% fruit skin is still as on the first day of observation only slightly wrinkled. The color change was also very different between the control and concentration treatments. In terms of tomato fruit weight, the smallest loss value compared to other concentrations was found in the 25% edible coating concentration treatment from an initial weight of 72 grams to 69.2 grams on the twelfth day, only losing 2.8 grams in weight.